Dietary LC-PUFA in iron-deficient anaemic pregnant and lactating guinea pigs induce minor defects in the offsprings' auditory brainstem responses. (12th December 2016) - Jougleux, Jean-Luc; Rioux, France M.; Church, Michael W.; Fiset, Sylvain; Jacques, Hélène; Surette, Marc E.
Abstract : Objectives : We previously demonstrated that a mild pre-natal/early post-natal iron-deficient anaemic (IDA) diet devoid of long-chain polyunsaturated fatty acids (LC-PUFA) affected development, neurophysiology, and cerebral lipid biochemistry of the guinea pigs' progeny. Impacts of dietary LC-PUFA on altered cerebral development resulting from pre-natal IDA are unknown. To address this health issue, impacts of mild gestational IDA in the presence of dietary LC-PUFA on the offsprings' neural maturation were studied in guinea pigs using auditory brainstem responses (ABRs) and assessments of brain fatty acids (FAs). Methods : Female guinea pigs ( n = 10/group) were fed an iron sufficient (IS) or IDA diet (146 and 12.7 mg iron/kg, respectively) with physiological amounts of LC-PUFA, during the gestation and lactation periods. From post-natal day (PNd) 9 onwards, the IS + PUFA diet was given to both groups of weaned offspring. Cerebral tissue and offsprings' ABR were collected on PNd24. Results : There was no difference in peripheral and brainstem transmission times (BTTs) between IS + PUFA and IDA + PUFA siblings ( n = 10/group); the neural synchrony was also similar in both groups. Despite the absence of differences in auditory thresholds, IDA + PUFA siblings demonstrated a sensorineural hearing loss in the extreme range of frequencies (32, 4, and 2 kHz), as well as modified brain FA profiles compared to the IS + PUFA siblings. Discussion : The present study reveals that siblings born from dams exposed to a moderate IDA diet including balanced physiological LC-PUFA levels during pregnancy and lactation demonstrate minor impairments of ABR compared to the control siblings, particularly on the auditory acuity, but not on neural synchrony, auditory nerve velocity and BTT.